Analysis of the Influence of Education Level, Age, Marital Status and Gender on Waiting Time for Educated Workers in Mataram City - Aswaria Aswaria; Gusti Ayu Arini; Ahmad Zaenal Wafik (Future Techno-Science, 2025)
The imbalance between the number of workforce and the amount of job opportunities has resulted in the emergence of unemployment problems for educated workers. This study aims to analyze the influence of variables of education level, age, marital status and gender on the waiting time for educated workers in Mataram City. Data collection was carried out by means of questionnaires distributed directly to educated workers who had completed D3 and S1 education in Mataram City to a sample of 100 respondents. The analysis method used in this study is multiple regression analysis. The results of the study indicate that the variable of education level has a negative and significant effect on the waiting time for educated workers in Mataram City. The variables of age and gender have a positive and significant effect on the waiting time for educated workers in Mataram City. The variable of marital status does not have a positive and significant effect on the waiting time for educated workers in Mataram City. The variables of education level, age, marital status and gender together have a positive or negative and significant effect on the waiting time for educated workers in Mataram City.